Grammatical Errors in Using the Simple Present Tense in Writing Descriptive Texts - Martina Napratilora; Ahlis Sarah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Simple present tense was often used by students in writing and speaking, so they needed to know and understand how to use it correctly, especially in writing descriptive texts. In reality, students still make various mistakes in using the simple present tense, including errors in writing nominal sentences, such as incorrect subject-verb agreement, improper placement of